TRANSLATION STRATEGIES FOR ENGLISH EPONYMS IN UZBEK: LINGUISTIC AND CULTURAL CHALLENGES (World Bulletin of Social Sciences, 2026)
Eponyms constitute a significant component of English vocabulary and frequently appear in scientific, cultural, and everyday discourse. Since eponyms are derived from proper names, they often carry historical, cultural, and semantic connotations that may create difficulties in translation. This paper examines translation strategies used for English eponyms in Uzbek and analyzes the linguistic and cultural challenges that arise during the translation process. The research applies a comparative and descriptive method to analyze selected English eponyms and their Uzbek equivalents in dictionaries, media texts, and scientific literature. The findings show that translators mainly employ strategies such as transliteration, calque translation, descriptive translation, and borrowing. The study concludes that successful translation of eponyms requires not only linguistic competence but also cultural awareness and knowledge of the historical background of the term. The results of this research may contribute to translation studies, lexicography, and contrastive linguistics.